Village-Owned Enterprises Management for Local Economic Growth: Pengelolaan Usaha Milik Desa untuk Pertumbuhan Ekonomi Lokal - Febrianti, Ais Arfia; Rodiyah, Isnaini (Indonesian Journal of Cultural and Community Development, 2025)
General Background: Village-Owned Enterprises (BUMDes) serve as a strategic instrument to stimulate local economic activities and improve rural welfare. Specific Background: Effective management of BUMDes depends on the ability of village governments to implement principles of transparency, accountability, and innovation. Knowledge Gap: Many studies address BUMDes’ role but rarely focus on managerial performance and organizational effectiveness at the village level. Aims: This study aims to analyze the management practices of BUMDes in supporting economic development and local revenue. Results: Findings show that well-managed BUMDes contribute significantly to village income and employment, while mismanagement—due to weak planning, lack of supervision, and low community participation—hampers progress. Novelty: The research integrates classical management theories (Terry, Fayol, Robbins) with the current operational model of BUMDes to evaluate management effectiveness comprehensively. Implications: Enhancing managerial skills, implementing financial transparency, and strengthening human resource capacity are vital for BUMDes sustainability. Highlights: BUMDes drives rural economic independence. Weak planning reduces managerial effectiveness. Governance reform strengthens local enterprise success.